MicroRNA-195-5p Downregulation Inhibits Endothelial Mesenchymal Transition and Myocardial Fibrosis in Diabetic Cardiomyopathy by Targeting Smad7 and Inhibiting Transforming Growth Factor Beta 1-Smads-Snail Pathway - Ding, Huaisheng; Yao, Jianhui; Xie, Hongxiang; Wang, Chengyu; Chen, Jing; Wei, Kaiyong; Ji, Yangyang; Liu, Lihong (Frontiers in Physiology, 2021)
Diabetic cardiomyopathy (DCM) is a complication of diabetes mellitus, which is associated with fibrosis and microRNAs (miRs). This study estimated the mechanism of miR-195-5p in endothelial mesenchymal transition (EndMT) and myocardial fibrosis in DCM. After the establishment of DCM rat model, miR-195-5p was silenced by miR-195-5p antagomir. The cardiac function was measured and miR-195-5p expression in myocardial tissue was detected. Myocardial fibrosis and collagen deposition, and levels of fibrosis markers were detected. Human umbilical vein endothelial cells (HUVECs) were exposed to high glucose (HG) and miR-195-5p was silenced. The levels of fibrosis proteins, endothelial markers, fibrosis markers, EndMT markers and TGF-β1/Smads pathway related proteins were measured in HUVECs. The interaction between miR-195-5p and Smad7 was verified. In vivo, miR-195-5p was highly expressed in myocardium of DCM rats. Inhibition of miR-195-5p reduced cardiac dysfunction, myocardial fibrosis, collagen deposition and EndMT. In vitro, HG-induced high expression of miR-195-5p and silencing miR-195-5p inhibited EndMT. In the mechanism, miR-195-5p downregulation blocked EndMT by inhibiting TGF-β1-smads pathway. Smad7 was the direct target of miR-195-5p, and silencing miR-195-5p inhibited EndMT by promoting Smad7 expression. Collectively, silencing miR-195-5p inhibits TGF-β1-smads-snail pathway by targeting Smad7, thus inhibiting EndMT and alleviating myocardial fibrosis in DCM.